Descriptive Study of Personal Hygiene and Length of Contact in Persons Affected by Leprosy in the Work Area of South Buano Health Center in Waisala District West Seram Regency In 2017 - Risman Tunny (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
Nowadays there are a lot of immunity diseases experienced by the community, one of which is leprosy. Leprosy is a chronic disease caused by the bacteria Mycobacterium leprae (M. leprae). The first time it attacks the peripheral nervous system, it can then attack the skin, mucosa (mouth), upper respiratory tract, endothelial reticule system, eyes, muscles, bones and testes. Leprosy is generally found in developing countries. As a result of the country's limited ability to provide adequate services in the fields of health, education, socio-economic prosperity in the community The purpose of this study was to Describe Personal Hygiene and Length of Contact in Persons Affected by Leprosy in the Work Area of South Buano Health Center in Waisala District, West Seram Regency The research used is analytic descriptive research using the Observational approach. The sample used was 30 respondents. Data collection was done by questionnaire by direct interview. The collected data is then processed and analyzed using the Microsoft Excel program computer and the Statistical Program (SPSS) version 24. From the results of the personal Hygiene analysis both were 10 respondent (33%) and the bad was 20 respondents (67%). Keywords :, Personal Hygiene, Length of Contact